Social Media, Friendships, and Financial Literacy Drive Millennial Investments: Media Sosial, Pertemanan, dan Literasi Keuangan Mendorong Investasi Milenial - Nesti Istichomah; Wisnu Panggah Setiyono (Academia Open, 2024)
This study explores the factors influencing millennial interest in investing, focusing on social media usage, investment understanding, and friendships. Using a quantitative approach, data was gathered from 100 respondents through questionnaires and analyzed with IBM SPSS 16. The results indicate that social media usage, investment knowledge, and friendships each significantly affect millennials' interest in investing, both individually and collectively. These findings highlight the pivotal role of digital platforms, financial literacy, and social networks in shaping investment behaviors among millennials. Highlight: Social media usage significantly influences millennials' investment interest. Investment understanding is crucial for millennials' investment decisions. Friendships play a key role in shaping millennial investment behaviors. Keywoard: Millennials, Investing, Social Media, Financial Literacy, Friendships